On a p-Laplacian system with critical Hardy–Sobolev exponents and critical Sobolev exponents - Nyamoradi, N. (Український математичний журнал, 2012)
We consider a quasilinear elliptic system involving the critical Hardy–Sobolev exponent and the Sobolev exponent. We use variational methods and analytic techniques to establish the existence of positive solutions of the system. Розглянуто квазiлiнiйну елiптичну систему з критичними показниками Хардi – Соболєва та Соболєва. Iз застосуванням варiацiйних методiв та аналiтичного пiдходу встановлено iснування додатних розв’язкiв системи.